Distributed systems in one lesson what a day in a coffee shop can teach us about distributed storage, computation, messaging, and consensus - Berglund, Tim (O'Reilly Media, 2015)
"Using a series of examples taken from a fictional coffee shop operation, this video course with Tim Berglund helps you explore five key areas of distributed systems, including storage, computation, timing, communication, and consensus. You'll also learn about some distributed programming paradigms. If you're an experienced developer looking to sharpen your architectural skills--particularly with regard to big data--this is one course you shouldn't miss. Dive into the five main problems areas in distributed systems--storage, computation, messaging, timing, and consensus, understand key challenges that emerge in each of these areas as you move from single-processor to a distributed architecture, discover one or more common open-source products that address each problem area."--Resource description page.